PENILAIAN KERENTANAN DAN KAPASITAS MASYARAKAT DALAM MENGHADAPI BAHAYA BANJIR LAHAR DI KECAMATAN SALAM KABUPATEN MAGELANG MENGGUNAKAN METODE SIG PARTISIPATIF - , Haruman Hendarsah, S.ST, Dr. Djarot Sadharto W., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Located in southwestern slope of Merapi Volcano, Salam sub-district is categorized as lahars prone area, since there are four rivers in this area through which lahars flow. The study is aimed to identify the characteristic of lahars and its elements at risk in Salam sub-district. The vulnerability and coping capacity of the community were assessed by investigating their perception and their responds to the lahars. The participatory GIS has also been examined to design policy on disaster risk reduction by involving their aspiration. Survey and observation on site methods was used in this research. Hazard assessment was done using Participatory GIS methods. P-GIS methods activities conducted through Focus Group Discussions and involves the participation of respondent, while the community perception was investigated through intense interview. Quota sampling method was used to select 180 respondents on village based. The study found that Villages around Kali Putih and Kali Blongkeng i.e. Jumoyo, Gulon, Seloboro and Sirahan are recognized as more vulnerable area. Social vulnerability of respondents is mostly classified in to moderate (51.11 % of respondents) and high level (42.78 % of respondents). All buildings in any type are categorized as vulnerable elements at risk, depending upon their location. The experience of the community on coping with lahars event forms good understanding to the hazard as indicated by their perception and builds high capacity as shown by their responds to the last lahars event. As one of conclusion, participatory GIS is proven as effective tool to involve the community in study area on designing policy for disaster risk reduction.